Festival des Arts Electroniques : Rennes. - Guzman, Antonio (Rennes : Ville de Rennes, 1986)
Sonnier, Keith ; Brown, Tony ; Molnar, Vera ; Bazile - Bustamante ; Holzer, Jenny ; Kowalski, Piotr ; Weiner, Lawrence ; Klein, Yves ; Beuys, Joseph ; Baquie, Richard ; Vivenza, Jean-Marc ; Shaw, Jeffrey ; Arman ; Orlan ; Allen, Terry ; Anderson, Laurie ; etc.
Festival des Arts Electroniques : Rennes du 7 au 14 Juin 1986
boek
Keywords: Rennes